Review of Liquid Nitrogen Quick-freezing Technology in Food - Zhao Yuanheng; Guo Jia; Chen Liubiao; Gu Kaixuan; Wang Junjie (Zhileng xuebao)
Liquid nitrogen quick-freezing technology enables food to pass quickly through the ice crystal area, and results in total or partial vitrification, which improves the quality of food and has been widely used in the food cold chain. In this study, the basic principles and classic heat transfer model of the liquid nitrogen quick-freezing technology are briefly introduced, and the characteristics of quick-freezing methods such as liquid nitrogen immersion freezing, cold-air circulation freezing, and spray freezing are compared. A thorough quality evaluation of quick-freezing food and research progress on applications of the quick-freezing technology are conducted. Finally, future research directions for the liquid nitrogen quick-freezing technology are considered.